Brain water content, glucose transporter densities and glucose utilization after 3 days of water deprivation in the rat - Duelli, Roman; Maurer, Martin H.; Heiland, Sabine; Elste, Volker; Kuschinsky, Wolfgang (Neuroscience letters, 1999)
After 3 days of water deprivation, the following parameters were measured in rats: (i) brain water content (apparent diffusion coefficient); (ii) local cerebral glucose utilization (LCGU) ([14C]deoxyglucose method) and (iii) densities of glucose transporters Glut1 and Glut3 (immunoautoradiography). The results show that brain water content is maintained after water deprivation. Densities of glucose transporters Glut1 and Glut3 increased in parallel to increased LCGU in some of the osmoregulatory structures indicating a long-term local adaptation of glucose transporters to LCGU.
Gesehen am 19.05.2021